HEAT PUMP STATION WITH CARBON DIOXIDE AS A WORKING FLUID ENERGY EFFICIENCY GROWTH IN COMBINED DISTRICT HEATING SYSTEM DUE TO ITS CONTROL SYSTEM OPTIMIZATION - Sit B.M.; Juravleov A.A.; Sit M.L. (Problems of the Regional Energetics, 2008)
A diagram of the heat pump station (HPS) for the central heat supply station of the district heating system, which gets the power from the CHP plant is examined. A block diagram of the control of the system and compressor pressure control system are examined. The description of the control laws of evaporator at the variable heat load of the HPS and control laws of the gas cooler taking into account the goal of achieving the maximum of COP of HPS is shown as well.